Rupture of a Non Coronary Sinus of Valsalva Aneurysm in Side the Right Atrium ...................................IJMTFM (2011) 1(2):70-74 - Papavdi, Asteria; Spanoudaki, Elpida; Nathena, Despoina; Michalodimitrakis, Emmanouil (International Journal of Medical Toxicology and Forensic Medicine, 2012)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> Background:Abnormalities of the sinus of Valsalva are usually congenital and quite rare among other heart deficiencies. They are frequently presented with aneurysm formation and the symptoms raised because of their existence vary. When rupture of an aneurysm occurs –more often in the right chambers of the heart -severe complications as cardiogenic shock arise. During a ten year period (2001-2011), in archives of Laboratory of Forensic Sciences of University of Crete only one case of natural death due to rupture of sinus of Valsalva s aneurysm is recorded. The authors present the case of a 53-year-old male, with no previous medical records, who suffered a sudden witnessed death. Dissecting the right atrium of the heart, an aneurysm of the sinus of Valsalva whose dimensions were 4X5 cm was detected. The aneurysm presented on its surface a linear rupture whose length was 2,7 cm. Aneurysm s formation, when not congenital, may be induced either by atheromatosis or less frequently by trauma, endocarditis ,syphilis or even Marfan s syndrome. Early diagnosis is possible through angiography, Doppler echocardiography, CT or MRI imaging. Key words: Sinus of Valsalva, aneurysm, cardiac tamponade, heart failure